1993
DOI: 10.1172/jci116350
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of renin-angiotensin system blockade on atherogenesis in cholesterol-fed rabbits.

Abstract: To investigate the mechanism by which angiotensin-converting enzyme (ACE) inhibition attenuates atherogenesis, we have studied the effects of a nonsulfhydryl ACE inhibitor, enalapril, and an angiotensin receptor antagonist, SC-51316, in cholesterol-fed rabbits. After 3 mo of enalapril treatment (10 mg/kg per d, p.o.) the percent plaque areas in the thoracic aortas of treated animals were significantly reduced (controls: 86.8±3.5%; treated: 31.1±8%, P < 0.001). Aortic cholesterol content was also reduced (contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0
1

Year Published

1994
1994
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(57 citation statements)
references
References 43 publications
3
53
0
1
Order By: Relevance
“…This was first shown with the ACE inhibitor captopril in Watanabe heritable hyperlipidemic rabbits. 13 Subsequently, similar results have been reported in other animal models of atherosclerosis, including genetically modified mice, 14 as well as rabbits 15 and monkeys 16 fed an atherogenic diet. The present study suggests that AT 1 receptor blockade blunts the development of atherosclerosis in the absence of a blood pressure-lowering effect.…”
Section: See P 1586supporting
confidence: 52%
“…This was first shown with the ACE inhibitor captopril in Watanabe heritable hyperlipidemic rabbits. 13 Subsequently, similar results have been reported in other animal models of atherosclerosis, including genetically modified mice, 14 as well as rabbits 15 and monkeys 16 fed an atherogenic diet. The present study suggests that AT 1 receptor blockade blunts the development of atherosclerosis in the absence of a blood pressure-lowering effect.…”
Section: See P 1586supporting
confidence: 52%
“…10 Angiotensin (Ang) II, the main effector of the renin-angiotensin system, plays an essential role in the regulation of blood pressure but is also involved in remodeling of the arterial wall. 11 It has recently been shown that antagonists of AT 1 Ang II receptors decrease the formation of the atheromatous plaque in several animal models of atherosclerosis 12,13 and that Ang II increases leukocyte adhesion to the endothelium in vitro. 14 Given that VCAM-1 expression in endothelial cells is inhibited by AT 1 receptor antagonists in vivo, 15 we hypothesized that Ang II could directly modulate VCAM-1 expression in these cells.…”
mentioning
confidence: 99%
“…However, alacepril decreased LDL levels and increased HDL levels in monkeys fed a highcholesterol diet. This finding has not been observed with non-sulfhydryl ACE inhibitors (10,20). It is also thought that the sulfhydryl group in alacepril may affect the lipid metabolism.…”
Section: Discussionmentioning
confidence: 82%
“…These findings suggest that the effects of antioxidants on atherosclerosis may be species specific. In the present study, we evaluated the antiatherosclerotic effects of a sulfhydryl-containing ACE inhibitor in monkeys fed a high-cholesterol diet, whereas other studies have indicated that non-sulfhydryl ACE inhibitors also attenuate the development of atherosclerosis in rabbits (20) and monkeys (10). Therefore, the antioxidative effects of the sulfhydryl group of alacepril are apparently unrelated to the prevention of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%